Sustainable Amazonian Landscapes Project - Quintero, Marcela; Castañeda Álvarez, Nora P.; Sachet, Erwan; Tello Dagua, Jhon Jairo; Valencia Gómez, Jefferson (2015)
Colombia and Peru host together 23% of the Amazon. Both countries are committed to reduce their greenhouse gases emissions, improve national and local capacities to adapt to climate change, enhance local livelihoods in forests and reduce net deforestation.